Poética da distopia no tempo presente : a narrativa da série Black Mirror - Costa, Angélica de Almeida (2019)
This study brings discussions about dystopias of the present time, using the Black Mirror series as a triggering narrative of questions. Russel Jacoby helps us with the concept of dystopia, which is the opposite of utopia, and shows the current social conventions extrapolated to the fullest, in their worst sense. In them, the collective welfare is substituted by the individual welfare, where monetary values can be attributed to objects and to human beings. We use the series form, in which the episodes are independent, and we work on a thoughts mosaic with themes that cross the narratives. Three episodes were chosen to be described, and have their writing unfolded in chapters that bring subjects such as social control and vigilance, dystopias and technologies. We also seek narrative intertextualities of other productions with the series with themes that approach contemporary activities of control, of daily actions and of subjects subjectivation. Zygmunt Bauman’s liquid figure is a metaphor for behavior in the present time, and supports the discussion about ways of life. Muniz Sodré and his thoughts on mediatisation of society support the argumentation about technologies and individuals. We evoke the authors such as Guy Debord, and his critique of spectacle society, Fernanda Bruno, Michel Foucault and Gilles Deleuze with the themes and discussions the series trigger, like vigilance, social obedience and discipline. These subjects helped us build a poetics of dystopia of the present time.